Information architecture for the world wide web - Morville, Peter (O'Reilly, 2006)
Introducing information architecture. Basic principles of information architecture. Process and methodology. Information architecture in practice. Information architecture in the organization. Case studies: MSWeb an enterprise intranet, an online community.